Hacia la determinación de la competitividad de la Pyme latinoamericana (By determining the competitiveness of the Latin American SMEs) - Camarena Adame, María Elena (Facultad de Contaduría Pública y Administración U.A.N.L., 2014)
Abstract. The aim of this review is to present the content and contribution of the book "determining the competitiveness of the Latin American SMEs". For this reason this paper is divided into 4 sections: Introduction, analysis, conclusion and bibliography. It is considered that the most important contribution of this book is that it shows how the model of systemic competitiveness can be applied to determine the competitiveness of SMEs, provided a complete diagnosis of their competitive position.